Practical Protocols for the Preparation of Highly Enantioenriched Silyl Ethers of (R)-3-Hydroxypentan-2-one, Building Blocks for the Synthesis of Macrolide Antibiotics - Seiple, Ian B.; Hog, Daniel T.; Myers, Andrew G. (Synlett, 2016)
Methacrolein is transformed in three steps to (R)-3-tert-butyldiphenylsilyloxypentan-2-one or (R)-3-tert-butyldimethylsilyloxypentan-2-one, compounds which serve as building blocks for the construction of macrolide antibiotics. The route is practical, highly enantioselective, and easily scaled.
Keywords: enantioselective synthesis; macrolide antibiotics; asymmetric addition; organozinc reagent; Nugent protocol